Polymorphism in Toll-Like Receptors and Helicobacter Pylori Motility in Autoimmune Atrophic Gastritis and Gastric Cancer - De Re, Valli (Cancers (Basel), 2019)
Autoimmune atrophic gastritis (AAG) is associated with an increased risk of certain types of gastric cancer (GC). Helicobacter pylori (H. pylori) infection may have a role in the induction and/or maintenance of AAG and GC. Toll-like receptors (TLR) are essential for H. pylori recognition and subsequent innate and adaptive immunity responses. This study therefore aimed to characterize TLR polymorphisms, and features of bacterial flagellin A in samples from patients with AAG (n = 67), GC (n = 114) and healthy donors (HD; n = 97). TLR5 rs5744174 C/C genotype was associated with GC, lower IgG anti H. pylori response and a higher H. pylori flagellin A abundance and motility. In a subset of patients with AAG, H. pylori strains showed a reduction of the flagellin A abundance and a moderate motility compared with strains from GC patients, a prerequisite for active colonization of the deeper layers of the mucosa, host immune response and inflammation. TLR9 rs5743836 T allele showed an association with serum gastrin G17. In conclusion, our study suggests that alterations of flaA protein, moderate motility in H. pylori and two polymorphisms in TLR5 and TLR9 may favor the onset of AAG and GC, at least in a subset of patients. These findings corroborate the function of pathogen–host cell interactions and responses, likely influencing the pathogenetic process.